Représentations de la conjugalité et stratégies de placement sur le marché matrimonial - Lukinson Jean; Ketleine Charles; Marie-Claire Reid (Enfances, Familles, Générations)
Research Framework: This article falls within the field of the sociology of conjugality, drawing on the concepts of “conjugal construction” and “conjugal cycle” proposed by Kaufmann (2014), alongside notions of plural and temporal socialization. It explores the representations that Haitian university students develop with regard to marriage and romantic relationships, while analyzing the impact of religious and familial norms on union formation processes.Objectives: The aim of the study is to analyze the affective strategies adopted by young women and men enrolled in a Haitian university, as well as the ways in which they construct their conjugal trajectories and negotiate the social norms associated with their romantic relationships.Methodology: The analysis is based on semi-structured interviews with students at a Haitian university, designed to gather their perceptions, experiences, and life stories relating to conjugality, marriage, and sexuality.Results: The romantic trajectories studied reveal a strong economic and gendered dimension. Faced with the risk of breaking up, young women in particular tend to stage their “conjugal seriousness.” The differentiated perception of the “conjugal cycle” also reflects a tension between personal aspirations and gendered social control.Contributions: The article sheds light on the strategies used by young people to position themselves within the matrimonial market and the meanings they attribute to their sexual and romantic practices in Haiti. It also highlights the effects of temporal and moral socialization on the management of romantic relationships in a context of strong normativity.